let I1 be set ; :: thesis: for I2 being non empty set
for f being Function of I1,I2
for A being ManySortedSet of I1
for B being ManySortedSet of I2
for M being ManySortedFunction of A,B * f holds ((id B) * f) ** M = M

let I2 be non empty set ; :: thesis: for f being Function of I1,I2
for A being ManySortedSet of I1
for B being ManySortedSet of I2
for M being ManySortedFunction of A,B * f holds ((id B) * f) ** M = M

let f be Function of I1,I2; :: thesis: for A being ManySortedSet of I1
for B being ManySortedSet of I2
for M being ManySortedFunction of A,B * f holds ((id B) * f) ** M = M

let A be ManySortedSet of I1; :: thesis: for B being ManySortedSet of I2
for M being ManySortedFunction of A,B * f holds ((id B) * f) ** M = M

let B be ManySortedSet of I2; :: thesis: for M being ManySortedFunction of A,B * f holds ((id B) * f) ** M = M
let M be ManySortedFunction of A,B * f; :: thesis: ((id B) * f) ** M = M
A1: now :: thesis: for i being object st i in I1 holds
( (B * f) . i = B . (f . i) & ((id B) * f) . i = id ((B * f) . i) )
let i be object ; :: thesis: ( i in I1 implies ( (B * f) . i = B . (f . i) & ((id B) * f) . i = id ((B * f) . i) ) )
assume A2: i in I1 ; :: thesis: ( (B * f) . i = B . (f . i) & ((id B) * f) . i = id ((B * f) . i) )
hence A3: (B * f) . i = B . (f . i) by FUNCT_2:15; :: thesis: ((id B) * f) . i = id ((B * f) . i)
( ((id B) * f) . i = (id B) . (f . i) & f . i in I2 ) by ;
hence ((id B) * f) . i = id ((B * f) . i) by ; :: thesis: verum
end;
now :: thesis: for i being object st i in I1 holds
(((id B) * f) ** M) . i = M . i
A4: (id B) * f is ManySortedFunction of B * f,B * f
proof
let i be object ; :: according to PBOOLE:def 15 :: thesis: ( not i in I1 or ((id B) * f) . i is M3( bool [:((B * f) . i),((B * f) . i):]) )
assume i in I1 ; :: thesis: ((id B) * f) . i is M3( bool [:((B * f) . i),((B * f) . i):])
then ((id B) * f) . i = id ((B * f) . i) by A1;
hence ((id B) * f) . i is M3( bool [:((B * f) . i),((B * f) . i):]) ; :: thesis: verum
end;
let i be object ; :: thesis: ( i in I1 implies (((id B) * f) ** M) . i = M . i )
assume A5: i in I1 ; :: thesis: (((id B) * f) ** M) . i = M . i
then A6: M . i is Function of (A . i),((B * f) . i) by PBOOLE:def 15;
( ((id B) * f) . i = (id B) . (f . i) & f . i in I2 ) by ;
then A7: ((id B) * f) . i = id (B . (f . i)) by MSUALG_3:def 1;
(B * f) . i = B . (f . i) by A1, A5;
hence (((id B) * f) ** M) . i = (id ((B * f) . i)) * (M . i) by
.= M . i by ;
:: thesis: verum
end;
hence ((id B) * f) ** M = M ; :: thesis: verum